Investigation of thrombin generation assay to predict vaso-occlusive crisis in adulthood with sickle cell disease - Feugray, Guillaume; Kasonga, Fiston; Grall, Maximilien; Dumesnil, Cécile; Benhamou, Ygal; Brunel, Valery; Le Cam Duchez, Véronique; Lahary, Agnès; Billoir, Paul (Frontiers in Cardiovascular Medicine, 2022)
Introduction Sickle cell disease (SCD) is an inherited hemoglobinopathy disorder. The main consequence is synthesis of hemoglobin S leading to chronic hemolysis associated with morbidity. The aim of this study was to investigate Thrombin Generation Assay (TGA) to assess hypercoagulability in SCD and TGA parameters as biomarkers of vaso-occlusive crisis (VOC) risk and hospitalization within 1 year. Materials and methods We performed TGA in platelet poor plasma (PPP) with 1 pM of tissue factor and 4 μM of phospholipid-standardized concentration, in duplicate for patients and controls. We measured thrombomodulin (TM), soluble endothelial Protein C Receptor and Tissue Factor Pathway Inhibitor (TFPI). Results A total of 113 adult patients with SCD, 83 at steady state and 30 during VOC, and 25 healthy controls matched on age and gender were included. Among the 83 patients at steady state, (36 S/S-1 S/β0, 20 S/Sα3.7, and 19 S/C-7 S/β+) 28 developed a VOC within 1 year (median: 4 months [2.25–6]). We observed an increase of peak and velocity associated with a shortening of lagtime and time to peak (TTP) and no difference of endogenous thrombin potential (ETP) in patients compared to controls. TFPI (p < 0.001) and TM (p = 0.006) were significantly decreased. TGA confirmed hypercoagulability in all SCD genotypes and clinical status. The association of ETP > 1,207 nM.min and peak >228.5 nM presented a sensitivity of 73.5% and a specificity of 93.9% to predict VOC development within 1 year. Conclusion We have demonstrated a hypercoagulable state in SCD associated with chronic hemolysis. These preliminary findings suggest that TGA parameters, as ETP and peak, could be used to predict VOC development within 1 year.